Comparative study between photodynamic and antibiotic therapies for treatment of footpad dermatitis (bumblefoot) in Magellanic penguins (Spheniscus magellanicus) - Nascimento, Cristiane Lassalvia; Ribeiro, Martha Simoes; Sellera, Fabio Parra; Pereira Dutra, Gustavo Henrique; Simoes, Alyne; Teixeira, Carlos Roberto [UNESP] (Elsevier B.V., 2015)
Background: Bumblefoot, referring to bed-sore-like foot lesions, is one of the most important clinical complications in captive birds and has a multifactorial etiology. Photodynamic therapy has been proposed as an alternative treatment for localized infections in response to the escalating problem of antibiotic resistance. The aim of this study was to compare outcomes in a group of captive Spheniscus magellanicus with bumblefoot lesions treated with photodynamic therapy (PDT) or antibiotics (ATB).Methods: Ten captive Magellanic penguins with preexisting stage III bumblefoot lesions were selected and randomly divided into one PDT and one ATB group, each including 11 pelvic-limb lesions. All animals underwent surgical debridement of lesions. In the ATB group, antibiotic ointment was applied topically three times a week, and systemic antibiotic and anti-inflammatory drugs were administered daily. In the PDT group, photodynamic therapy was applied three times a week without the use of topical or systemic medication. Lesion areas were photographed, and swabs were collected for culture and sensitivity, on the first day and every 14 days for a total of 84 days. The four species of bacteria showing the most resistance to the antibiotics screened on. the antibiogram were used to determine resistance to PDT with an in vitro test.Results: There were significant differences in healing rate and average healing time between the PDT and ATB groups (63.62% vs. 9.09% and 42 vs. 70 days, respectively).Conclusion: The findings of this study attest to the effectiveness of photodynamic therapy for the treatment of stage III bumblefoot in Spheniscus magellanicus. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: Captivity; Bed sore; Photodynamic inactivation; Pododermatitis; Rehabilitation